Implementation of the norwegian 'Starting right' child health service innovation: implementation adjustments, adoption, and acceptability - Thomas Westergren; Eirin Mølland; Kristin Haraldstad; Åshild Tellefsen Håland; Unni Mette Stamnes Köpp; Liv Fegran; Eirik Abildsnes (BMC, 2021)
Abstract Background An increased and/or stable proportion of the child and adolescent population reports symptoms of impaired health, and the symptoms can be identified early. Therefore, structured child- and parent-reported outcome measures need to be implemented in child and school health services for decision support and identification of children at risk. We aimed to (a) qualitatively examine adjustments of active implementation from the pilot implementation of the Norwegian 'Starting Right' health service innovation including an online child health assessment tool and practical routines, and (b) measure practitioners´ adoption and parental acceptability. Methods We used a mixed-methods design to qualitatively examine adjustments from working notes and meeting memoranda, and quantitatively assess adoption and acceptability from user rates provided by the systems log. Twenty-one child and school health nurses (CSHNs) from two child health centers participated in the implementation pilot of online health assessments in children aged 2-, 4- and 6-year. We used a deductive and narrative analysis approach using Fixsen et al.´s core implementation components to code and sort adjustments. Results Core implementation components were adjusted throughout the pilot implementation. Researchers´ increased their availability in reciprocity with staff evaluation to integrate active implementation adjustments. We launched a project for improved data systems integration. The overall CSHNs adoption rate was satisfactory and higher in center A, where a medical secretary supported the nurses through the entire pilot phase, than in center B (96 vs. 55 %). Parental acceptability rate was overall high (77 %) with increased rates among parents of 6-year-old children (98 %) compared with younger ones (78-85 %), and in cases where both parents received the questionnaires. Conclusions The 'Starting Right' health service innovation implementation was actively adjusted by integration of core implementation components mainly based on staff evaluation. The CSHNs adopted the innovation which was also acceptable to parents.